CODEIGNITER (CI) FRAMEWORK ON ADMIN E-COMMERCE MONITORING INFORMATION SYSTEM - Nurul Fiona Damayanti; Fitrah Rumaisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
E-commerce at this time is a very profitable business. E-commerce has excellent potential in terms of sellers who want a more comprehensive range of products and increased turnover. At the same time, buyers feel a sense of security when making transactions due to a system that can monitor both tracking and delivery and the results of product reviews that have been purchased based on previous purchases. All of this is inseparable from the admin system, which can control and monitor all transaction flows that occur. The application uses a framework that can support all of this and a programming language that can be used as a reference for creating an e-commerce admin system which uses: MySQL, PHP, CSS, HTML, and CodeIgniter as a framework that can unite everything, while for a more responsive display using bootstrap. Making this system is implemented into a website-based application. The purpose of this research is to develop admin features from the results of previous research data where the average e-commerce admin system is still semi-manual. Hence, researchers are interested in creating a monitoring information system that can monitor the flow of transactions, where the involvement is buyers, sellers, and couriers as the main objects.